IDENTIFICATION AND RISK ASSESSMENT OF KETAK HANDICRAFT SMEs IN THE MIDDLE OF THE COVID-19 PANDEMIC - Wafiah Murniati; Hairul Fahmi (Center for Study and Journal Management FTI UMI, 2022)
Uncertainty in conditions driven by external factors from the threat of the virus that has an impact on restrictions on human movement by the government affects business and economic conditions in Indonesia, including Small and Medium Enterprises (SMEs) in handicrafts. The business processes carried out by SMEs are inseparable from the risks they face. Risk management is the right strategy in tackling risks that occur throughout the business process. The purpose of this study was to identify and conduct an assessment of the risks faced by SMEs in Central Lombok during the Covid-19 Pandemic. The method used to analyze risk factors is the checklish method and the Analytical Hierarchy Process (AHP). All risks that SMEs may face have been identified, classified and ranked according to risk exposure. The results showed that there were 4 risk factors and 11 risk subfactors identified. The most critical risk comes from financial risk. There was a decrease in income during Covid-19, a decrease in the level of consumer purchasing power, and limited capital. Limited human resource capabilities if marketing online and the difficulty of obtaining raw materials are also critical risks faced by SME actors during the Covid-19 Pandemic